DETERMINAN PERILAKU MEROKOK PADA REMAJA DI KOTA PADANG TAHUN 2023 - handayani, sri (E-Jurnal Medika Udayana; Vol 13 No 6 (2024): E-Jurnal Medika Udayana, 2024)
The World Health Organization (WHO) in 2012 showed that Indonesia was ranked third with the largest number of smokers in the world after China and India. Riskesdas data shows that the smoking behavior of people aged 15 years and over has not decreased from 2013 to 2018, tends to increase from 32.8 percent in 2013 to 33.8 percent in 2018. The behavior of people aged 15 years and older has increased. The aim of this research is to determine the determinants of smoking behavior in Padang city teenagers in 2023. The type of research used was descriptive analytical funding with a cross sectional design, which was carried out in July-October 2023. The population in this study were all young men at SMP Negeri 15 Padang. The sample was taken using a total random sampling method of 87 people. Data collection was carried out through questionnaires. Then processed with SPSS and analyzed with the Chi-square test with a degree of significance (a = 0.05). The results of the research showed that as many as (74.7%) students smoked and had a negative attitude (50.6%), there was parental influence (41.4%) and there was (48.3%) peer influence. Factors of smoking behavior in teenagers at SMP N 15 Padang are attitude (p= 0.008), parental influence (p= 0.028), peer influence (p= 0.016). Based on the results of this research, it can be concluded that all independent variables are related to the dependent variable. To minimize the incidence of smoking behavior among students at SMP Negeri 15 Padang, it is hoped that there will be cooperation between the school and parents, such as providing education about the dangers of smoking.